Design, Construction and Experimental Verification of Magnetorheological Brake - Polcar, Petr (Communications - Scientific letters of the University of Zilina, 2013)
This article deals with the principle, design and verification of the magnetorheological brake. Physical principles, possible designs and advantages of magnetorheological brakes are presented. A design is chosen, simulated and device is built. Simulations are compared with results obtained from measurements on the device, suitable magnetorheological fluid is chosen and torque characteristics of the brake are experimentally verified.